Environmental Education and Teacher Development: Engaging a Dual Curriculum Challenge - Chris Reddy (Environmental Association of Southern Africa, 2011)
Few events in South Africa have been as dramatic and sudden as the demise of apartheid (the institutionalised separation of 'races' in all spheres of life) and the introduction of a majority, multi-party government by democratic process in 1994. The events immediately following the demise of apartheid prompted a series of changes in the political and economic systems of the country. While political reorientation and economic redress were of immediate concern, there was also an acknowledgement of the importance of educational change in the rebuilding of the country. Lotz and Olivier (1998) indicate that the change in government in 1994 has enabled fundamental change in the education policy environment in South Africa, which is primarilyaimed at transformation at systemic, social and methodological levels. Johnson (1997) notes that educational policy changes are potentially far-reaching in that the proposals for education transformation are situated within a broader strategy for national reconstruction and development. Hargreaves (1998:vii), in writing about educational change in the United States of America, mentions that, [e]ducation change is everywhere. Never have so many schools and their teachers had to deal with so much of it. Responding to wide-ranging educational reform is an inescapable reality of teachers' work in the United States and most other advancedindustrial nations as well. Although this quotation refers to the United States, it is applicable and relevant to the current South African context, where widespread changes have been proposed for education at all levels. These changes needed to occur in a very compressed time frame. Polyzoi and Cerna (2001:64) suggest that educational changes under such conditions are like a 'living laboratory' that is different from the situation in more developed countries, where change occurs in an 'essentially stable societal context'.